(untitled) (Philosophy and Progress, 2016)
Within patriarchy men enjoy almost absolute authority that relegates women to a seemingly powerless entity. India is a case in point. However, historically mothers have often been instrumental in parental control in Indian households. According to Hagans Powercontrol theory of gender difference in risk preference, sons are subjects to weaker maternal parental control because they are mostly occupied with the outer world. Hence, unlike daughters in a patriarchal household, they are more risk prone and delinquent. On the other hand, daughters are generally risk averse for their mothers direct instrumental control. They deploy a powerful emotional intelligence through strong interpersonal network. This paper argues that R. K. Narayan in Grandmothers Tale takes such aspects of feminine strength into consideration and relays that through the story of Bala, as told to him by her grandmother; thereby revealing a kind of position of power for women in society which can be characterized as low patriarchy. By depicting different levels of parental control placed upon children in her story, Grandmother raises the narrator of the story in a female-headed household which induces him into understanding the differences between him and children brought up under patriarchy. This paper will explore how the narrator, along with his Grandmother, advocates a new domestic sphere where male and female children can be equally dutiful and well-behaved through the intervention of higher feminine intelligence and low patriarchy. Philosophy and Progress, Vol#55-56; No#1-2; Jan-Dec 2014